2015
DOI: 10.1016/j.tws.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic crushing and energy absorption of sandwich structures with combined geometry shell cores

Abstract: a b s t r a c tDynamic crushing and energy absorption characteristics of sandwich structures with combined geometry shell cores were investigated experimentally and numerically. The effect of strain rate on the crushing behavior was presented by the crushing tests at quasi-static, intermediate and high strain rate regimes. It was shown that absorbed energy increased with increasing impact velocity. The effect of confinement on crushing behavior was shown by conducting confined experiments at quasi-static and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The quasi-static and dynamic deformation behavior of the tested as received combined geometry shells and their sandwiches were recently investigated in Refs. [29] and [30] by the same authors. Previous results revealed that failure/fracture of few specimens occurred during crushing, imparting the energy dissipating capability.…”
Section: Introductionmentioning
confidence: 92%
“…The quasi-static and dynamic deformation behavior of the tested as received combined geometry shells and their sandwiches were recently investigated in Refs. [29] and [30] by the same authors. Previous results revealed that failure/fracture of few specimens occurred during crushing, imparting the energy dissipating capability.…”
Section: Introductionmentioning
confidence: 92%
“…The values of the contact energy E c versus the corresponding values of the peak load F max were plotted in a bilogarithmic scale and a linear regression was realised to determine the contact parameters (n, K i ), as presented in Figure 15; the value of n was obtained by the slope a of the linear equation according to equation (5) and the value of K i by the constant term b of the linear equation according to equation (6).…”
Section: Energy Balance Modelmentioning
confidence: 99%
“…An advantage of sandwich structures is that it is possible to design them in order to obtain the desired properties according to their specific application by varying different parameters (materials and thicknesses of core and face sheet), filling them with foam [5], applying GFRP outer skins [4], using different and innovative types of core (core with combined geometry shells [6], open-cell truss core [7], ‘tied-core’ [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on sandwich structures mainly focus on bending properties, [1][2][3][4][5][6] compressive properties, [7][8][9][10][11][12] and energy absorption properties. [13][14][15][16][17][18][19][20] The basic form of the sandwich structure currently used in engineering applications consists of two thin, strong face plates and a lightweight core material that is filled between the face plates and firmly connected to them. There are many materials used for the face plates, such as aluminum, stainless steel, composite laminates etc.…”
Section: Introductionmentioning
confidence: 99%